BaR-SPOrt: The instrument to be accommodated at Dome C - ZANNONI, MARIO; BOELLA, GIULIANO FILIPPO; SIRONI, GIORGIO; GERVASI, MASSIMO; Carretti, E; Cortiglioni, S; Macculi, C; Ramponi, M; Sbarra, C; Ventura, G; Monari, J; Poloni, M; et al. (E D P SCIENCES, 2005)
The BaR-SPOrt (Balloon-Borne Radiometers for Sky Polarization Observations) experiment, a program of the Agenzia Spaziale Italiana (ASI) co-funded by PNRA (Progetto Nazionale di Ricerca in Antartide) was originally designed as a payload for long duration balloons flights. The changing scenario, both scientific and strategic, has led us to propose it for the starting winter campaign of at the Concordia Base. Here the instrument and the features making it suitable to operate at Dome-C are described. After the initial setup, BaR-SPOrt should not require any kind of routine intervention by a dedicated base staff. The experiment will just need electrical power (less than 2 kW) and a suitable accommodation on the field. It can be fully monitored and controlled, including the data acquisition, through its own telemetry/telecommand link using IRIDIUM modems. Both the receiver and the critical electronics are housed inside a temperature-controlled vacuum chamber, providing the properly stabilized environment. The cold part of the radiometer employs a closed loop mechanical cryo-cooler that provides temperatures < 70 +/- 0.1 K with low power consumption (< 200 W).